Recent Progress of ZnO-Based Nanoparticle: Synthesizing Methods of Various Dopant and Applications - Nurlaela rauf (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
This review focus on the effect of doping rare earth metals, transition metals, noble metals, poor metals, and non-metals on ZnO nanoparticles. ZnO is a semiconductor material with an average wide energy band gap of 3.2 eV. The doping is used to improve the properties of ZnO which strongly depend on their application. The concentration of doping, the type of doping and the process using sol-gel, hydrothermal and precipitation methods are affected in modifying the ZnO lattice parameters. The transition metal widely used for photocatalysts and sensors. The doped application of ZnO nanoparticles as a semiconductor material has proven advantageous in enabling various photocatalytic, glucose biosensors, VOC detection sensors, antibacterial, biomedical, and optoelectronic spintronic, LED, NLO, and silicon solar cells. This review provided information for scientist in choosing the synthesizing methods of ZnO with desired properties and application in future.